DEPOSITIONAL AND TECTONIC FRAMEWORK OF THE RIFT BASINS OF LAKE BAIKAL FROM MULTICHANNEL SEISMIC DATA - Hutchinson D.R.; Golmshtok A.J.; Zonenshain L.P.; Moore T.C.; Scholtz C.A.; Klitgord K.D. (My University, 1992)
Recent multichannel seismic reflection data from Lake Baikal, located in a large, active, continental rift in central Asia, image three major stratigraphic units totaling 3.5 to 7.5 km thick in four subbasins. A major change in rift deposition and faulting between the oldest and middle-rift units probably corresponds to the change from slow to fast rifting in early Pliocene time inferred from on-land studies. A minor modification of fault patterns characterizes the youngest unit. A brief comparison of the basins of Lake Baikal with those of the East African rift system highlights differences in structural style that can be explained by differences in age and evolution of the surrounding basement rocks.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен